The pesticides law under the optics of rural producers - Marques, Mauricio Dias; Braga Junior, Sergio Silva; Forti, Juliane Cristina (Interações, 2019)
The aim of the current study is to understand the perceptions of rural producers about the procedure for reverse logistics of empty pesticide packages proposed by Brazilian legislation. The research was conducted in Interior of the State of São Paulo for application to 48 small and medium-sized rural producers. As a result, it was found that producers generally do not meet the legal requirements and that one of the possible causes may be the lack of inspection by the Public Authorities